2022
DOI: 10.1002/dev.22234
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences predict neurite density differences in young children with and without attention deficit hyperactivity disorder

Abstract: Adverse childhood experiences (ACEs) put millions of children at risk for later health problems. As childhood represents a critical developmental period, it is important to understand how ACEs impact brain development in young children. In addition, children with attention‐deficit/hyperactivity disorder (ADHD) are more likely than typically developing (TD) peers to experience ACEs. Therefore, the current study examined the impact of ACEs on early brain development, using a cumulative risk approach, in a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…This study (Hare et al, 2022) claimed that ACEs affect the axonal density in the corpus callosum, as well as affect the development of the cerebellum. These brain structures affect critical processes such as emotional regulation, linguistic processing, and visual‐spatial processing in children with ADHD (Hare et al, 2022). Furthermore, this study found that children with ADHD were more likely than typically developing (TD) peers to experience ACEs (Hare et al, 2022).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…This study (Hare et al, 2022) claimed that ACEs affect the axonal density in the corpus callosum, as well as affect the development of the cerebellum. These brain structures affect critical processes such as emotional regulation, linguistic processing, and visual‐spatial processing in children with ADHD (Hare et al, 2022). Furthermore, this study found that children with ADHD were more likely than typically developing (TD) peers to experience ACEs (Hare et al, 2022).…”
Section: Resultsmentioning
confidence: 96%
“…Generally, each study reported lower brain volumes in children who have experienced stressful life events and have ADHD. Both studies investigated brain volume, but one study (Hare et al, 2022) investigated the cerebellum, corpus callosum, orbitofrontal cortex, amygdala, hippocampus, and anterior cingulate. This study (Hare et al, 2022) claimed that ACEs affect the axonal density in the corpus callosum, as well as affect the development of the cerebellum.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations